Investigating educational leadership practices among school leaders in Malaysia Schools - Hashim, Che Noraini; Razikin, Mohyani; Yusof, Mohd Yusnan; Abdul Rashid, Adnan; Syed Hassan, Sharifah Sariah (EuroJournals Publishing, Inc., 2010)
The best practice of school leadership has always been investigated in the context of Western perspectives and theories. Nevertheless, the values and spirituality framework of school leadership have not been explored extensively. Empirical evidence of the leadership practice model among the school leaders is crucial in determining the direction of the management and values integrated. This study was designed with two-fold purpose. Firstly,it attempted to validate a proposed model of school leaders’ practices among the principals in West Malaysian secondary schools. Secondly, it investigated the relationships between the integration of Islamic values, leadership principle, transformational leadership and leadership style. Using structural equation modeling, the study investigated the relationships between Islamic values, leadership principle and transformational leadership and leadership style. This study was based on the conceptual framework of Islamic leadership of Islamic worldviews by Alhabshi (1994) and Ibrahim Ahmad Bajunid (1996)and the model of leadership by Barrett (2006) and Bass and Avolio (1997). A selfconstructed instrument was deployed to 12 states in West Malaysia for 1440 samples. However, only 1290 responses were retrieved. The findings indicate that the hypothesized model has to be respecified. The evidence has shown that the school leaders must be value-driven specifically on fulfilling the needs and responsibilities to his or her staff. Then he or she is able to enhance the leadership behavior as well as practicing leadership principles. Thus, the leadership principles that the leader practices will influence the style of leadership which is democratic and an ideal way of ensuring success to the organization. The theoretical, methodological and practical contributions of the study are discussed.